Impact of socio-health factors on life expectancy in the low and lower middle income countries - Mondal, Md. Nazrul Islam; Shitan, Mahendran (Tehran University of Medical Sciences, 2013)
Background: This study is concerned with understanding the impact of demographic changes, socioeconomic inequalities, and the availability of health factors on life expectancy (LE) in the low and lower middle income countries.